Peranan Pemuda dalam Pendidikan Sosial Kemasyarakatan - Asichul In'am (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
Youth has a very important role in society. In community activities the role of youth cannot be underestimated in terms of programs, implementation to evaluation, it is youth who play a very important role here. Can be a benchmark of how the role of youth when participating in the implementation of religious activities both in the community or in educational institutions. The dominant role of youth in society is the role in the religious and social fields. In the religious field, youth can carry out learning activities, especially among children who are hungry for knowledge about religion. In the social field, youth can participate and even become an example in carrying out activities held by the local community, such as community service, greening, environmental cleanliness and others. All of these things will be able to run smoothly when the younger generation can fill activities with positive things.